2019
DOI: 10.1158/1078-0432.ccr-18-3295
|View full text |Cite
|
Sign up to set email alerts
|

Drugs That Modify Cholesterol Metabolism Alter the p38/JNK-Mediated Targeted and Nontargeted Response to Alpha and Auger Radioimmunotherapy

Abstract: Purpose: For the development of new anticancer therapeutic radiopharmaceuticals, including alpha particle emitters, it is important to determine the contribution of targeted effects in irradiated cells, and also of nontargeted effects in nonirradiated neighboring cells, because they may affect the therapeutic efficacy and contribute to side effects.Experimental Design: Here, we investigated the contribution of nontargeted cytotoxic and genotoxic effects in vitro and in vivo (in xenografted mice) during alpha (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…It could also be related to the enhancement of immunogenicity by radiation, as we already demonstrated for the B16F10 melanoma model [53], also consistent with the increased expression of inflammatory genes shown by transcriptomics. Additional studies need to be conducted to confirm that these pathways are involved in the NRAS Q61K 1007 response to [ 131 I]ICF01012-TRT, as modified lipid metabolism has already been reported to alter the efficiency of radioimmunotherapy [54]. In previous studies, we showed that TRT reduces hematogenous dissemination, especially lung invasion [21], by modifying pseudoepithelial-mesenchymal transition pEMT-mechanisms [24].…”
Section: Discussionmentioning
confidence: 79%
“…It could also be related to the enhancement of immunogenicity by radiation, as we already demonstrated for the B16F10 melanoma model [53], also consistent with the increased expression of inflammatory genes shown by transcriptomics. Additional studies need to be conducted to confirm that these pathways are involved in the NRAS Q61K 1007 response to [ 131 I]ICF01012-TRT, as modified lipid metabolism has already been reported to alter the efficiency of radioimmunotherapy [54]. In previous studies, we showed that TRT reduces hematogenous dissemination, especially lung invasion [21], by modifying pseudoepithelial-mesenchymal transition pEMT-mechanisms [24].…”
Section: Discussionmentioning
confidence: 79%
“…For example, both JNK [33] and p38 MAP kinases [34] were previously suggested to take part in membrane-associated HSP25 induction. Of note, cholesterol depletion inhibited JNK and p38 MAP kinase-associated signaling in different model systems [35,36]. Thus, it is tempting to speculate that MβCD-or nystatin-induced PM modifications impair different signaling cascades towards HSF1 resulting in an altered PTM profile.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the contribution of targeted and nontargeted effects, we used a Bliss independence mathematical model [ 22 , 56 ]. It is essential to notice that donor cells are, in reality, at the same time donor and recipient cells (i.e., irradiated cells secrete substances toward neighboring irradiated cells).…”
Section: Methodsmentioning
confidence: 99%
“…The precise nature of factors that mediate the nontargeted effect is unknown, but reactive oxygen and nitrogen species (ROS/RNS) and various cytokines have been involved [ 17 , 18 , 19 ]. Other studies [ 20 , 21 , 22 ] have also demonstrated the involvement of plasma membrane signaling in the bystander effect via the generation of ceramide (considered as a mediator of radiation), leading to activation of the mitogen-activated protein kinases (MAPK) and other pathways, which then transduce amplified signals into the nucleus.…”
Section: Introductionmentioning
confidence: 99%